Does Online-Formed Peer Relationship Affect Academic Motivation During Online Learning? - Ignasia Geralda Vania; Whisnu Yudiana; Hery Susanto (Journal of Educational, Health and Community Psychology, 2022)
The Covid-19 pandemic has caused most schools and universities in Indonesia to face a new learning situation called Pembelajaran Jarak Jauh (PJJ) or online learning. Furthermore, this situation also has an impact on first-year students who are about to enter higher education. As the pandemic gets worse, they are not able to get to know their social and academic environment face-to-face. Thus, this study aimed to find the role of online-formed peer relationships on students' academic motivation during the online learning period. Based on a sample of 118 first-year students from a university, this study found that participants had a high quality of peer relationships and academic motivation. Moreover, peer relationships significantly predict students' academic motivation. However, participants who had interacted entirely online with their friends had a significantly lower quality of peer relationships. This result suggests the importance of building good peer relationships to support students' academic motivation, especially in the pandemic.